"Mi'jita, What for?" Exploring Bicultural Identity of Latina/Chicana Faculty and Implications for Supporting Latinx Students in Social Work. Issue 2 (May 2019) - Mendoza, Natasha S.; Lechuga-Peña, Stephanie; Lopez, Kristina; Jackson, Kelly F.
Latinx faculty have an opportunity to influence a growing population of incoming Latinx students. As Chicana/Latina social work faculty, we seek to raise consciousness about our biculturalism and demonstrate how it could play a role in educating students. To that end, we highlight issues related to language. The meaning of language is complex, manifesting personally and politically. It is unclear how the relationship between identity and language intersect for individuals working in higher education. Thus, we draw on a theoretical model of bicultural competence and testimonios or first-person narratives to explore these issues in-depth, extrapolate meaning from experience, and report implications for research, teaching, and practice.